2020
DOI: 10.35974/isc.v7i1.1045
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Directed Reading Thinking Activity Strategy to Enhance Students’ Reading Comprehension

Abstract: Introduction: The purpose of the study is to find out the improvement of student’ reading comprehension through Directed Reading Thinking Activity Strategy. This study was designed to find out the answer to the following question: Is there any significant difference in reading comprehension achievement before  and after giving DRTA treatment?. Method: The instrument used for this study is reading comprehension test, which contained 30 question and administreted to SMP Advent II Bandung.The respondent of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The result of this research was actually supported by some research of (Lubis, 2018;Megawati, 2019;Nerim, 2020;Novendiana et al, 2016;Panjaitan & Siagian, 2020;Setiartin, 2018). Those research also found that DRTA strategy was effective to teach reading.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The result of this research was actually supported by some research of (Lubis, 2018;Megawati, 2019;Nerim, 2020;Novendiana et al, 2016;Panjaitan & Siagian, 2020;Setiartin, 2018). Those research also found that DRTA strategy was effective to teach reading.…”
Section: Discussionsupporting
confidence: 74%
“…One of the strategies that can be used by the teacher of reading in order to involve the students to participate actively is Directed Reading Thinking Activity or DRTA strategy. DRTA is a strategy where the students should make prediction on the content of the text based on the guided questions from the teacher and prove their prediction in the text they read (Panjaitan & Siagian, 2020). Further, DRTA will help students to comprehend a text by activating their background knowledge related to the text.…”
Section: Introductionmentioning
confidence: 99%
“…Agustiani (2016) also found out that DRTA along with literature circles were effective in improving the reading comprehension achievement of narrative texts of the Grade 10 learners of Baturaja University in Indonesia. Another study on the effectiveness of DRTA among grade VII learners revealed that DRTA strategy has positive effect in improving the students' reading skills (Panjaitan, N. B., & Siagan, Y.L., 2020). Similarly, Satriani, et.…”
Section: Introductionmentioning
confidence: 89%
“…al. (2022), Panjaitan and Siagan (2020) and Suico (2022) that DRTA is effective in improving the reading comprehension skills of the learners.…”
Section: Common Reading Miscues Of the Respondentsmentioning
confidence: 99%
“…This further concludes that using Directed Reading Thinking Activity is an effective strategy for teaching reading. Directed Reading Thinking Activity is an effective method in improving students' reading skills as emphasized by the "The Use of Directed Reading Thinking Activity Strategy to Enhance Students' Reading Comprehension" [11].…”
Section: Significant Difference Between the Level Of Narrative Text R...mentioning
confidence: 99%